Probabilitas Penerapan dan Konsep Hybrid e-voting dalam Penyelenggaraan Pemilihan Umum 2024 - Muhammad Addi Fauzani; Anis Banowati; Dandi Dwie Lisadi (Prosiding Seminar Hukum Aktual Fakultas Hukum Universitas Islam Indonesia, 2023)
This study aims to analyze, first, the reliability of the implementation of hybrid e-voting in the implementation of the 2024 Election. Second, the concept of hybrid e-voting in the implementation of elections in Indonesia in the future. Research is included in normative juridical with legal and contextual approaches. The research concludes that first, despite having a strong legal basis, hybrid e-voting cannot yet be implemented in the 2024 Election for several reasons, namely: a) there is no agreement between the legislators and election organizers; b) the stages of the 2024 Election are still directed at conventional Elections; c) the absence of comprehensive implementing regulations for e-voting. Second, the concept of hybrid e-voting in the future can be implemented by preparing \regulation, institutions, facilities and infrastructure, election participants and voters from society.